Coercive concern nationalism, liberalism, and the schooling of Muslim youth - Jaffe-Walter, Reva. (Stanford Stanford University Press, 2016)
Many liberal-minded Western democracies pride themselves on their commitments to egalitarianism, the fair treatment of immigrants, and the right to education. These environments would seem to provide a best-case scenario for the reception of immigrant youth. But that is not always the case. Coercive Concern explores how stereotypes of Muslim immigrants in Western liberal societies flow through public schools into everyday interactions, informing how Muslim youth are perceived by teachers and peers. Beyond simply identifying the presence of racialized speech in schools, this book uncovers how coercive assimilation is cloaked in benevolent narratives of care and concern.
Includes bibliographical references and index.
Keywords: Muslim youth--Education--Denmark.